Using biometric data in software engineering: a systematic mapping study. Issue 9 (4th July 2021) - Menzen, Juliano Paulo; Farias, Kleinner; Bischoff, Vinicius
ABSTRACT: The use of biometric data (BD) records promises to advance the software engineering field. The rapid adoption of wearable computing technology has widely increased the amount of BD records available. Several aspects about the use of BD records in software engineering field are unknown, such as body measurements used to support daily tasks, and empirical methods that are used to evaluate their benefits. Consequently, a thorough understanding of state-of-the-art techniques still remains limited. This article, therefore, aims at providing a classification and a thematic analysis of studies on the use of BD records in the context of software development. Moreover, it seeks to introduce a classification taxonomy, and pinpoints research gaps, challenges and trends. A systematic mapping of the literature was designed and performed based on well-established practical guidelines. In total, 40 primary studies were analysed and categorised, which were selected by applying a careful filtering process from a sample of 3930 studies to answer seven research questions. Over 77% of articles use more than one biometric aspect to analyse tasks performed by developers; over 47% of articles used eye-track sensor to analyse biometric factors, followed by brain-wearable sensors with 40%, skin sensor with 22%, cardiac sensor with 20%, and others fewer representatives; most studies analysed had their quality assessed as high; most studies were published in journal. This study provides a systematic map of studies that use BD records in software engineering, thereby serving as a basis for future research.